1997
DOI: 10.1002/(sici)1096-9861(19971110)388:1<120::aid-cne8>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of neurons immunoreactive for parvalbumin and calbindin in the somatosensory thalamus of the raccoon

Abstract: The aim of this study was to assess the distribution of neurons immunoreactive for parvalbumin (PV), calbindin (CaBP), glutamic acid decarboxylase (GAD), and gamma-aminobutyric acid (GABA) in the somatosensory thalamus of the raccoon and to compare these features to those of other species, especially primates. Immunohistochemistry was used to study the location of these neurons in the ventroposterior nucleus (VP), ventroposterior inferior nucleus (VPI), posterior group of nuclei (Po), and reticular nucleus (Rt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…In particular, several lines of evidence have indicated that in thalamic nuclei these CaBPs are variously expressed in different mammalian species (Jones and Hendry 1989;Bentivoglio et al 1990;Rausell et al 1992;Arai et al 1994;De Biasi et al 1994a;Herron et al 1997) and during development (Frassoni et al 1991(Frassoni et al , 1998. In the adult rat thalamus PV is expressed only by neurons of the reticular nucleus (RT) and by axonal fibers and puncta in different nuclei of the dorsal thalamus (Celio 1990;Arai et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, several lines of evidence have indicated that in thalamic nuclei these CaBPs are variously expressed in different mammalian species (Jones and Hendry 1989;Bentivoglio et al 1990;Rausell et al 1992;Arai et al 1994;De Biasi et al 1994a;Herron et al 1997) and during development (Frassoni et al 1991(Frassoni et al , 1998. In the adult rat thalamus PV is expressed only by neurons of the reticular nucleus (RT) and by axonal fibers and puncta in different nuclei of the dorsal thalamus (Celio 1990;Arai et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Parv + somata have been found in other thalamic nuclei of non-rodent eutheria (e.g. macaque VP- Rausell et al, 1992; VP of the galago and Tupaia- Diamond et al, 1993;AV, LP, LGv of the guinea pig-De Biasi et al, 1994; VP of the raccoon- Herron et al, 1997). The relatively large number of Parv + somata in many thalamic nuclei of the echidna may be a consequence of the small size of the thalamic reticular nucleus in this monotreme.…”
Section: Distribution Of Calcium-binding Protein Immunoreactivity In mentioning
confidence: 99%
“…Somata immunoreactive for CB have been reported in midline thalamic nuclei (Re, PV, CeM), VM, LG, LD and Po (Celio, 1990;Frassoni et al, 1991;Arai et al, 1994). In non-rodent eutherians, somata immunoreactive for CB are found in the primate VPL (Rausell et al, 1992), primate LG (Diamond et al, 1993), primate pulvinar (Gutierrez et al, 1995) and raccoon VP, VPI and Po (Herron et al, 1997). In eutheria, the distribution of CB immunoreactivity is often reported to be complementary to that of Parv (Celio, 1990).…”
Section: Distribution Of Calcium-binding Protein Immunoreactivity In mentioning
confidence: 99%
See 1 more Smart Citation
“…In telencephalic regions, including cortical fields in mammals and parts of the avian pallium in birds (a brain region considered homologous as a field to the cortex, claustrum, and parts of the amygdala in mammals; see Reiner et al, 2004; Jarvis et al, 2005), these cells very often constitute a subpopulation of GABAergic interneurons (Hendry and Jones, 1991; Baimbridge et al, 1992; Rogers, 1992; Jones, 1993; Parent et al, 1995; DeFelipe, 1997; Pinaud et al, 2006a). Such correspondence, however, is not universal (Mize et al, 1991; Baimbridge et al, 1992; Behan et al, 1992; Mize, 1992; Jones, 1993; Herron et al, 1997). The expression of calbindin, and a related calcium‐binding protein, parvalbumin, has also been instrumental for the classification of nuclear subdivisions within the mammalian thalamus (Jones, 1998; Jones, 2001).…”
mentioning
confidence: 99%